Estudio de infección por Cryptosporidium spp. y otras parasitosis en la interfase animal doméstico-silvestre en humedales de Argentina - Berra, Yanina (2023)
Changes in the environment can increase the contact rate between wild and domestic species and favor the transmission of pathogens in both directions. Wetlands are among the most diverse and productive ecosystems in the world. In Argentina there are the San Nicolás Nucleus (SNN) in Esteros del Iberá and the Ciervo de los Pantanos National Park (CPNP) in the Lower Delta of Paraná River. Within its diverse fauna, the presence of the marsh deer (Blastocerus dichotomus)\nstands out, whose subpopulation in the Paraná Delta is categorized as "Endangered" and that of\nEsteros del Iberá as "Nearly Threatened". Both areas have undergone environmental modifications, predisposing to morbidity and mortality events in domestic and wild animal\npopulations associated with adverse climatic events, high parasite loads and infection by multihost parasites such as Cryptosporidium spp. whose risk of infection increases when a shared use\nof the environment occurs.\nThe general objective of this thesis is to analyze the eco-epidemiological factors associated with infection by nematodes and protozoa and to use Cryptosporidium spp. as an infection model\nin fecal samples from domestic (cows, horses, sheep, and dogs) and wild (marsh deer, capybaras, and gray fox) animal hosts that inhabit the SNN and CPNP.\nDuring 2017 and 2018, samples of fecal matter from the environment were obtained through\nconvenience sampling, with a transect line design in both study areas. The samples were georeferenced. Nine environmental variables were recorded for the classification of the transects\nin: core, interface and edge. The modified Wisconsin qualitative-quantitative technique was performed to determine the parasite load in eggs per gram (EPG) and oocysts per gram (OPG) and the parasite genera present. For the diagnosis of Cryptosporidium spp., the samples were concentrated and stained by modified Ziehl Neelsen. DNA was extracted and amplified by nestedPCR for the 18S rRNA gene (genus specific) and GP60 protein (C. parvum subtyping). The\nproducts obtained were purified for sequencing. Statistical and spatial analysis was performed\nand linear multivariate logistic regression models were developed.\nIn SNN, an anthropization gradient was observed, being higher in the border areas, and lower in the core areas. A total of 629 samples were collected, being the interface zone the one that presented significantly higher values of parasite load. A spatial cluster was identified for samples with a high HPG load located in an interface area that was associated with the presence of horses\nand capybaras, and with the cold season. In the CPNP, all the transects were classified as interface. A total of 159 samples were collected. The highest HPG values were found in dog\nsamples and the highest OPG values in capybara samples. The transect 1 (T1) had the highest values for the HPG and for the OPG, together with T4. Dog, marsh deer, and capybara samples were spatially associated. In total, 12 parasitic genera were identified, of which 6 were found in both domestic and wild species. It was determined 16.8% in SNN and 27,7% in CPNP of samples positive for Cryptosporidium spp. In both areas, the highest frequency was in marsh deer. 5,7%\nof the positive samples were confirmed by nested-PCR 18s rRNA and were negative for C. parvum subtyping. Sequencing did not present confirmatory results.\nIn Argentina, our results represent the first records of Cryptosporidium spp. in marsh deer, confirmed by genus-specific PCR. The first report of a positive sample in gray fox and the second for capybaras and horses in the country is also presented. In both the SNN and the CPNP, domestic-wild animal interface areas were determined where\ndomestic and wild animal species make shared use of the habitat and presented risk factors related to the parasite load of nematodes and protozoa, such as the season and the geographic\nlocation. Although the presence of Cryptosporidium spp. could not be confirmed with the complete\nmolecular protocol proposed, the presence of potentially zoonotic genotypes in the area is not\nruled out and that this agent is shared by the animal species under study. Anthropic impact is a\nproblem in natural areas, especially in interface zones, and could have an effect on the health of animal populations.\n